2023
DOI: 10.3390/su15108084
|View full text |Cite
|
Sign up to set email alerts
|

Assessing CO2 Emissions of Online Food Delivery in Japan

Abstract: The COVID-19 pandemic and the subsequent lockdown of cities have led to the rapid growth of online food delivery (OFD). Moreover, there are concerns that OFD platforms may impose offers on users in order to continue to increase their market share, leading to numerous environmental issues such as overconsumption and a significant increase in plastic packaging waste. Most studies have focused on the environmental impacts associated with food packaging and have been mostly limited to China. However, less research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Beyrouthy [59] reported that grocery and meal delivery segments of the OFD industry earned revenues that were more than double those of pre-pandemic levels. Hu et al [60] reported that in Japan, the OFD industry increased by 25% from 2016 to 2020, and it is set to increase by a further 17% from 2021 to 2025. South Korea's OFD industry sales have grown by an average of 85% over the past four years, achieving USD 14.3 billion in sales in 2020 [61].…”
Section: Single-use Plastic Pollution Through Online Food Delivery (O...mentioning
confidence: 99%
“…Beyrouthy [59] reported that grocery and meal delivery segments of the OFD industry earned revenues that were more than double those of pre-pandemic levels. Hu et al [60] reported that in Japan, the OFD industry increased by 25% from 2016 to 2020, and it is set to increase by a further 17% from 2021 to 2025. South Korea's OFD industry sales have grown by an average of 85% over the past four years, achieving USD 14.3 billion in sales in 2020 [61].…”
Section: Single-use Plastic Pollution Through Online Food Delivery (O...mentioning
confidence: 99%
“…Jepang adalah ekonomi terbesar ketiga, setelah AS dan China, dan merupakan mitra terbesar kedua Uni Eropa (UE), setelah China. Jepang dan Cina menyumbang lebih dari sepertiga dari PDB dunia (Dreher, 2006;Hu et al, 2023;Shahbaz et al, 2018). Uni Eropa berusaha untuk merundingkan Perjanjian Perdagangan Bebas (FTA) dengan Jepang untuk mempromosikan pembangunan ekonomi yang berkelanjutan di kedua wilayah.…”
Section: Pendahuluanunclassified